2019
DOI: 10.1159/000494116
|View full text |Cite
|
Sign up to set email alerts
|

Multivessel Coronary Revascularization Strategies in Patients with Chronic Kidney Disease: A Meta-Analysis

Abstract: Background: Early revascularization can lead to better prognosis in multivessel coronary artery disease (CAD) patients with chronic kidney disease (CKD). However, whether coronary artery bypass grafting (CABG) or percutaneous coronary intervention (PCI) is better remains unknown. Methods: We searched PubMed and the Cochrane Library database from inception until December 9, 2017, for articles that compare outcomes of CABG and PCI in multivessel CAD patients with CKD. We pooled the odds ratios with a fixed-effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 52 publications
1
11
1
Order By: Relevance
“…All included studies were considered of high quality because the NOS scores were not less than 7 for each study (Table 2 ). Table 3 summarising all other meta‐analysis papers 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 on this topic.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All included studies were considered of high quality because the NOS scores were not less than 7 for each study (Table 2 ). Table 3 summarising all other meta‐analysis papers 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 on this topic.…”
Section: Resultsmentioning
confidence: 99%
“…Table 3 summarising all other meta-analysis papers [42][43][44][45][46][47][48][49][50][51][52] on this topic.…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
“…While CABG was reported to be associated with a higher risk of short-term mortality and stroke, MI and repeat revascularization were less frequent than in those who had undergone PCI in the long-term follow-up ( 3 , 4 , 13 , 14 ). The majority of these studies designated MACCE as the primary outcome and concluded CABG is associated with fewer adverse events in patients with CKD than in PCI ( 14 , 15 ). However, some studies have published contrary findings ( 16 , 17 ), most likely due to differences in the stent type and definitions of the primary outcome.…”
Section: Discussionmentioning
confidence: 99%
“…So this issue is very urgent and difficult. 43 Previous META analyses also studied similar content, but there were several limitations: [44][45][46] First, the targeted patient was patients with chronic kidney disease (eGFR < 60 ml/min/1.73 m 2 ), which included patients with mild to moderate renal failure. And the guidelines recommend mild to moderate renal failure patients with CAD undergo revascularization (PCI or CABG).…”
Section: Discussionmentioning
confidence: 99%